Cat and mouse in a haunted house - Stilton, Geronimo (New York : Scholastic, 2004)
Geronimo explores a haunted mansion populated by ghosts.
G2
Keywords: Mice -- Juvenile fiction; Animals -- Juvenile fiction; Ghost stories; Mice -- Fiction; Cats -- Fiction; Journalists -- Fiction; Halloween -- Fiction; Haunted houses -- Fiction; Mystery and detective stories; Humorous stories